Outcome and Predictors of Treatment Failure in Chronic Osteomyelitis Using Bioactive Glass Granules and Putty Formulations - Adriana Macedo Dell'Aquila; Gabriela Nagy Baldy dos Reis; Gabriel Trova Cuba; Walter Hamilton de Castro Targa; José Carlos Bongiovanni; Thomas Stravinskas Durigon; Mauro José Salles; Fernando Baldy dos Reis (MDPI AG, 2023)
Background: The aim of this study is to evaluate the outcome of patients with cavitary chronic osteomyelitis undergoing adjuvant treatment with bioactive glass (BAG) S53P4 and identify the independent risk factors (RFs) for recurrence in 6- and 12-month patient follow-up. Methods: A retrospective, multicentre observational study conducted in tertiary specialised hospitals among patients undergoing the surgical treatment of chronic cavitary osteomyelitis using BAG-S53P4 in a granule and/or putty formulation to assess the clinical outcome and RFs for failure in 6- and 12-month patient follow-up. Results: Of the 92 and 78 patients with 6-month and 12-month follow-ups, infection was eradicated in 85.9% and 87.2%, respectively. In the 6-month follow-up, BAG-S53P4 in the granule formulation presented a greater risk of recurrence compared to the bioactive glass putty formulation or combined granules and putty (prevalence ratio (PR) = 3.04; confidence interval 95% [CI95%]: 1.13-10.52) and neoplasia (PR = 5.26; CI95%: 1.17-15.52). In the 12-month follow-up cohort of 78 patients, smoking (PR = 4.0; 95% CI: 1.03-15.52) and nonfermenting GNB infection (PR = 3.87; CI95%: 1.09-13.73) presented a greater risk of recurrence. Conclusions: BAG-S53P4 is a viable option for bone-void filling and the treatment of chronic cavitary osteomyelitis. Formulations of BAG with putty or in combination with granules showed better results.